Effect of irrigation with saline water on phytoremediation of soil contaminated by Cadmium - SHEN Xingfeng; HAO Yingjun; REN Yizhuo; TANG Xiwang (Guan'gai paishui xuebao)
【Background and Objective】 Cadmium contamination is a ubiquitous soil environmental problem facing agricultural production in many countries. Phytoremediation is an environmentally friendly technique. Since bioavailability of Cd varies with biogeochemical environment which, in turn, is regulated by soil water, irrigation is likely to have an important influence on efficacy of phytoremediation. This paper presents the results of an experimental study on the effect of irrigation with saline water on phytoremediation of Cd-contaminated soil. 【Method】 Pots filled with soil containing Cd at content of 0, 5, 10 and 15 mg/kg were used in the experiment. All pots were grown with maize and were irrigated with deionized water (W1), natural saline water (W2), and water with NaCl at the same salinity as W2 (W3). In each treatment, we measured Cd absorption by the maize. 【Result】 ① When the soil Cd content was low, irrigation with saline water resulted in a reduction in plant height, root length, as well as in dry and fresh biomasses of both above and below-ground parts. However, an increase in soil Cd content significantly inhibited maize plant growth only in treatment W1, while no significant effects were observed in treatments W2 and W3. ② When Cd content was 5, 10, or 15 mg/kg, the impact of irrigation water on Cd content in the above- and below-ground parts of the maize seedlings was ranked in the order of W3 > W2 > W1. ③ When soil Cd content was 5 and 10 mg/kg, Cd accumulation in the above-ground parts of the maize seedlings was significantly lower in W2 and W3 than in W1 (P<0.05), while when soil Cd content was 15 mg/kg, there were no significant differences in Cd accumulation in the above-ground parts of the maize between the three water treatments (P˃0.05). When soil Cd content was 5, 10 or 15 mg/kg, there was no significant difference in Cd accumulation in the roots of the maize between the three water treatments (P˃0.05). 【Conclusion】 Irrigating maize with saline water reduces phytoremediation efficiency of Cd-contaminated soil when soil Cd content was low, while it had no noticeable impact when soil Cd content was high. Saline water can thus be used for phytoremediation of soils heavily contaminated by Cd in areas where freshwater is scarce.